Many shades of green: the dynamic tropical forest–savannah transition zones - Oliveras-Menor, I; Malhi, Y (Royal Society, 2016)
The forest-savanna transition is the most widespread ecotone in tropical areas, separating two of the most productive terrestrial ecosystems. Here we review current understanding of the factors that shape this transition, and how it may change under various drivers of local or global change. At broadest scales the location of the transition is shaped by water availability, mediated strongly at local scales by fire regimes, herbivory pressure and spatial variation in soil properties. The frequently dynamic nature of this transition suggests that forest and savanna can exist as alternative stable states, maintained and separated by fire-grass feedbacks and tree shade-fire suppression feedback. However, this theory is still contested and the relative contributions of the main biotic and abiotic drivers and their interactions are yet not fully understood. These drivers interplay with a wide range of ecological processes and attributes at the global, continental, regional and local scales. The evolutionary history of the biotic and abiotic drivers and processes plays an important role on the current distributions of these transitions as well as in their species composition and ecosystem functioning. This ecotone can be sensitive to shifts in climate and other driving factors, but is also potentially stabilised by negative feedback processes. There is abundant evidence that these transitions are shifting under contemporary global and local change, but the direction of shift varies according to region. However, it still remains uncertain how these transitions will respond to rapid and multi-faceted ongoing current changes, and how increasing human influence will interact with these shifts.